Engineering Polycentric Circular Waste Governance: A Policy-Engineering Framework for Indonesian Municipal Solid Waste Management - Kurtis Waite (SWATANTRA, 2025)
Municipal solid waste management has become one of the most urgent environmental governance challenges in rapidly urbanising countries. In Indonesia, this challenge is not only technical but also administrative, fiscal, behavioural, and institutional. National targets for waste reduction and waste handling have encouraged local governments to move beyond conventional collect-and-dispose systems, yet implementation gaps remain visible in collection coverage, source separation, recycling markets, landfill dependence, informal-sector integration, and data reliability. This article develops a policy-engineering framework for strengthening circular waste governance in Indonesian municipalities. It argues that municipal waste reform requires the integration of environmental engineering tools, polycentric public administration, community participation, and circular economy indicators. Using an integrative literature and policy review, the paper synthesises global waste management debates, Indonesian regulatory directions, and socio-technical transition theory. The analysis identifies five interdependent dimensions of circular municipal waste governance: institutional coordination, engineered infrastructure, data and performance metrics, community-based participation, and market-based circularity. The paper finds that circular waste systems cannot be achieved through infrastructure investment alone. They require local governments to redesign incentives, align responsibilities across administrative levels, standardise waste data, strengthen waste banks and community organisations, professionalise informal recovery networks, and connect engineering decisions with public accountability. The article contributes to public administration and environmental engineering by proposing a practical framework that can guide municipal planning, policy evaluation, and future empirical research.